Overall Impact of Coronavirus Disease 2019 Outbreak in Children With Functional Abdominal Pain Disorders: Results From the First Pandemic Phase. Issue 6 (December 2021) - Strisciuglio, Caterina; Martinelli, Massimo; Lu, Peter; Bar Lev, Michal Rozenfeld; Beinvogl, Beate; Benninga, Marc A.; Di Lorenzo, Carlo; Fiori Nastro, Francesca; Nurko, Samuel; Pearlstein, Haley; Rosen, Rachel; Shamir, Raanan; et al.
ABSTRACT: Objective: We aimed to assess how the first phase of coronavirus disease 2019 (COVID-19) pandemic influenced symptoms in children with functional abdominal pain disorders (FAPDs) and to characterize their quality of life (QoL), anxiety and global health. Methods: This was a multicenter, observational, international study conducted between April and July 2020 at six different referral centers. Children diagnosed with FAPDs between October 2019 and February 2020 were enrolled and prospectively interviewed at 4 months of follow-up during the first pandemic phase ( Quarantine group ). Patients were asked to complete PedsQL 4.0 Generic Core Scale and PROMIS Anxiety and Global Health questionnaires. A cohort of children diagnosed with FAPDs between October 2018 and February 2019 was used as a Control group . Results: Three-hundred-fifty-six children were enrolled of whom 180 (mean age at diagnosis: 14 ± 2.8 years) in the Quarantine group and 176 (mean age at diagnosis: 13 ± 2.8 years) in the Control group. At 4 months of follow-up, we observed a significant reduction of children reporting >5 episodes of abdominal pain per month when compared to baseline, in both groups ( Quarantine group : 63.9% vs 42.2%, P < 0.001; Control group : 83.5% vs 50%, P < 0.001). The Quarantine group had median QoL values of 84.8 with 16.6% of children showing high anxiety values and 55% having decreased global health score. Conclusions: We demonstrated symptoms' improvement at 4 months of follow-up in both cohorts. During the first months of the COVID-19 quarantine children with FAPDs showed satisfactory QoL and anxiety scores, suggesting positive effects of school closure and increased parental attention. Abstract : Supplemental Digital Content is available in the text